On the Move to Meaningful Internet Systems: OTM 2008 OTM Confederated International Conferences, CoopIS, DOA, GADA, IS, and ODBASE 2008, Monterrey, Mexico, November 9-14, 2008 Proceedings, Part I - Tari, Zahir (Information Systems and Applications, incl. Internet/Web, and HCI, 2008)
This two-volume set LNCS 5331/5332 constitutes the refereed proceedings of the five confederated international conferences on Cooperative Information Systems (CoopIS 2008), Distributed Objects and Applications (DOA 2008), Grid computing, high performAnce and Distributed Applications (GADA 2008), Information Security (IS 2008), and Ontologies, Databases and Applications of Semantics (ODBASE 2008), held as OTM 2008 in Monterrey, Mexico, in November 2008. The 86 revised full and 9 revised short papers presented together with 5 invited papers and 4 keynote talks were carefully reviewed and selected from a total of 292 submissions. Corresponding to the five OTM 2008 main conferences CoopIS, DOA, GADA, IS, and ODBASE the papers are organized in topical sections on Web service, business process technology, E-service management, distributed process management, schema matching, business process tracing, workflow and business applications, designing distributed systems, context in distributed systems, high availability, adaptive distributed systems, scheduling allocation, databases in grids, grid applications, data management and storage, new tendencies and approaches, intrusion detection, information hiding, data and risk management, access control, evaluation and implementation, semantic matching and similarity measuring, semantic searching, ontology development, ontology maintanence and evaluation, ontology applications, and semantic query processing.